Applied Multidimensional Systems Theory - Bose, Nirmal K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Revised and updated, this concise new edition of the pioneering book on multidimensional signal processing is ideal for a new generation of students. Multidimensional systems or m-D systems are the necessary mathematical background for modern digital image processing with applications in biomedicine, X-ray technology and satellite communications. Serving as a firm basis for graduate engineering students and researchers seeking applications in mathematical theories, this edition eschews detailed mathematical theory not useful to students. Presentation of the theory has been revised to make it more readable for students, and introduce some new topics that are emerging as multidimensional DSP topics in the interdisciplinary fields of image processing. New topics include Groebner bases, wavelets, and filter banks.
Multivariate Polynomial Fundamentals for Multidimensional Systems -- Multivariate Polynomial Positivity (Nonnegativity) Tests -- Multidimensional Sampling -- Multidimensional Digital Filter Recursibility and Stability -- 2-D Fir Filters, Linear Prediction adn 2-D IIR Filters -- Wavelets and Filter Banks.
Keywords: Signal processing; Computer vision; System theory; Control theory; Signal, Speech and Image Processing; Computer Vision; Systems Theory, Control